Mal de Debarquement syndrome: clinical cases and literature review - Paškonienė , A.; Poškutė , R.; Markevičiūtė , V.; Ivaška , J.; Lesinskas , E. (Neurologijos seminarai, 2018)
Background. Mal de Debarquement syndrome (MdDS) is a rare neuro-otologic disorder that mainly appears for middle-aged women and occurs after long-term passive motion (flight by plane, cruise). The syndrome symptoms can be persistent dizziness, sensation of rocking, unsteadiness, and disequilibrium. The syndrome diagnostics is complicated because there is no instrumental examination that could help to diagnose disorder thus neuro-otological examination is non-informative. The diagnosis is based on anamnesis, therefore, MdDS is often undiagnosed or inappropriate diagnosis is determined. To the knowledge of the authors, there are no publications on this syndrome in the Lithuanian language. Therefore, the aim of this article is to introduce this syndrome to Lithuanian doctors by presenting cases diagnosed in Lithuania and diagnostic criteria as well as by reviewing information published in the literature.Methods. Two clinical cases are described. Mal de Debarquement syndrome was diagnosed for two middle-aged women after air travel. Both women complained of sudden dizziness after the trip, however, neuro-otological examination had not revealed any pathology. In the literature review, 21 articles are overviewed describing the Mal de Debarquement syndrome.Results. Diagnostic criteria that helped to diagnose the Mal de Debarquement syndrome in 2016 are presented. A diagnostically significant feature of MdDS is a reduction in symptoms after the patient returns to passive motion. MdDS is often accompanied by anxiety and depression. Research shows that stress-reducing therapy, medications for migraine prophylactic, and lifestyle changes are effective in reducing symptoms and improving the quality of life.Conclusions. MdDS is still a rarely diagnosed disorder in many countries. Clinical symptoms and history of long-term passive motion is especially important for the diagnosis. Neurootological examination is required for differential diagnosis from other clinically similar diseases.
Keywords: Mal de Debarquement syndrome; dizziness; vestibular disorder